1980
DOI: 10.1128/aac.18.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Comparative In Vitro Appraisal of Piperacillin, Including Its Activity Against Salmonella typhi

Abstract: Piperacillin was evaluated in vitro against 711 clinical isolates of aerobic and anerobic gram-positive and gram-negative bacteria, including 76 isolates of Salmonella typhi. Piperacillin minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) were compared with those of a range of B8-lactam, aminoglycoside, and other antimicrobial agents, and inoculum size effects were considered. The relationship between dilution and disk diffusion tests was studied by regression analysis. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…and Klebsiella pneumoniae (4,11). In addition, several investigators have demonstrated in vitro synergism between piperacillin and aminoglycosides against members of the Enterobacteriaceae (5,8,12), Pseudomonas aeruginosa (2,8,13,17), and other nonfermentative, gramnegative bacteria (3).…”
mentioning
confidence: 99%
“…and Klebsiella pneumoniae (4,11). In addition, several investigators have demonstrated in vitro synergism between piperacillin and aminoglycosides against members of the Enterobacteriaceae (5,8,12), Pseudomonas aeruginosa (2,8,13,17), and other nonfermentative, gramnegative bacteria (3).…”
mentioning
confidence: 99%